(untitled) (Annals of Medical Research, 2022)
Aim: This descriptive and correlational study was conducted to examine the effects of postpartum support needs of mothers and the support they received on breastfeeding self-efficacy. Materials and Methods: The study was conducted in 431 mothers with 4-8 weeks old babies, who presented to Karaman city-center family health units between November 2019 and June 2020. For data collection, a personal information form, the Postnatal Support Scale (PSS), and the Breastfeeding Self-Efficacy Scale-Short Form (BSES) were used. In independent groups, t-test, one-way analysis of variance, Pearson correlation analysis, and multiple regression analysis were used. Results: The mean BSES score of the mothers included in the research was 57.53±11.36, the mean PSS Importance of Needs subdimension score was 168.48±20.32, and the mean PSS Support Received subscale score was 162.25±31.25. In the study, it was found that the BSES score was affected by the PSS Support Received subdimension score (p<0.001). Conclusions: In conclusion, as the postnatal support needs of the mothers increased, their breastfeeding self-efficacy scores decreased, and as the received postnatal support increased, their breastfeeding self-efficacy scores increased, as well. Midwives and other health professionals should provide support for the needs of mothers in the postpartum period, and also include family, relatives, and friends in this support process. In addition, midwives should encourage mothers and social support providers regarding breastfeeding and provide informative support.